Prevalence and antimicrobial resistance of MRSA across different pig age groups in an intensive pig production system in Australia. (27th May 2020) - Sahibzada, Shafi; Pang, Stanley; Hernández‐Jover, Marta; Jordan, David; Abraham, Sam; O'Dea, Mark; Heller, Jane
Abstract: This observational study aimed to determine MRSA prevalence using strain‐specific real‐time PCR at the pig level, stratified by age groupings, within a pig enterprise. A total of 658 samples were collected from individual pigs ( n = 618) and the piggery environment ( n = 40), distributed amongst five different pig age groups. Presumptive MRSA isolates were confirmed by the presence of mecA, and MALDI‐TOF was performed for species verification. All isolates were tested against 18 different antimicrobials. MRSA was isolated from 75.2% (95% CI 71.8–78.6) of samples collected from pigs, and 71% of the MRSA isolates from this source were identified as community‐associated (CA)‐MRSA ST93, while the remainder were livestock‐associated (LA)‐MRSA ST398. Amongst environmental isolates, 80% (CI 64.3–95.7) were ST93 and the remainder ST398. All MRSA isolates from pigs and the environment were susceptible to ciprofloxacin, gentamicin, linezolid, mupirocin, rifampicin, sulfamethoxazole–trimethoprim, teicoplanin and vancomycin. Phenotypic rates of resistance were penicillin (100%), clindamycin (97.6%), erythromycin (96.3%), ceftiofur (93.7%), chloramphenicol (81.2%), tetracycline (63.1%) and amoxicillin–clavulanate (63.9%). A low prevalence of resistance (9.2%) was observed against neomycin and quinupristin–dalfopristin. The probability of MRSA carriage in dry sows (42.2%) was found to be significantly lower ( p < .001) when compared to other age groups: farrowing sows (76.8%, RR1.82), weaners (97.8%, RR 2.32), growers (94.2%, RR 2.23) and finishers (98.3%, RR 2.33). Amongst different production age groups, a significant difference was also found in antimicrobial resistance for amoxicillin–clavulanate, neomycin, chloramphenicol and tetracycline. Using the RT‐PCR assay adopted in this study, filtering of highly prevalent ST93 and non‐ST93 isolates was performed at high throughput and low cost. In conclusion, this study found that weaner pigs presented a higher risk for CA‐MRSA and antimicrobial resistance compared to other age groups. These findings have major implications for how investigations of MRSA outbreaks should be approached under the One‐Health context.